2019
DOI: 10.1136/ijgc-2018-000046
|View full text |Cite
|
Sign up to set email alerts
|

Superficially invasive stage IA vulvar squamous cell carcinoma—therapy and prognosis

Abstract: ObjectivesSuperficially invasive stage IA squamous vulvar cancer (VSCC) is defined as a single lesion measuring ≤2 cm with a depth of invasion of ≤1.0 mm (FIGO stage IA). This article examines the natural course and prognosis of superficially invasive VSCC.MethodsThis is a retrospective case series of 46 patients (median age 58 years) with superficially invasive stage IA VSCC receiving wide local excision between January 1996 and November 2014 in the University Medical Center Hamburg-Eppendorf.ResultsMedian tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…Our case series confirmed that vulvar SISCCA is a rare entity with good prognosis, and, according to guidelines, surgical local excision without groin lymphadenectomy is a safe and effective treatment. However, we observed a higher relapse rate (21%) compared to the two other series of SISCCA [15,16] reported in the literature (8.7% and 5.9%, respectively).…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Our case series confirmed that vulvar SISCCA is a rare entity with good prognosis, and, according to guidelines, surgical local excision without groin lymphadenectomy is a safe and effective treatment. However, we observed a higher relapse rate (21%) compared to the two other series of SISCCA [15,16] reported in the literature (8.7% and 5.9%, respectively).…”
Section: Discussioncontrasting
confidence: 77%
“…Focusing on SISCCA, Grimm et al [15] reported the presence of lichen sclerosus and dVIN in all four reported recurrences. Similarly, in our series, dVIN was found in all patients who relapsed, but no significant differences were found with non-recurrent patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary tumor should be resected with at least 1 cm clear margins and either unilateral or bilateral inguinofemoral lymph nodes or in selected patients SLNs should be removed. There is no need for inguinofemoral lymphadenectomy for stage IA patients since risk for nodal involvement is <1% ( 38 ). But patients with stage IB or higher stages have ≥8% risk of nodal metastasis and lymphadenectomy is mandatory ( 39 ).…”
Section: Introductionmentioning
confidence: 99%